Chromosomal variations and genetic diversity in subpopulations of Senna alexandrina Mill. from Western Thar, India - Sunita Arora; Monika Vyas; Meena Barupal (Caryologia)
Homologous recombination promotes genetic diversity by exchanging genetic material between homologs, ensuring unique combinations of alleles in offspring. Karyomorphology of the chromosomes can prove to be an efficient tool to reveal the true nature of plant species at genetic level. In this context, our study analyzed the karyomorphology and male meiosis in a medicinal herb, Senna (Senna alexandrina Mill., Syn. Cassia angustifolia Vahl.), family Fabaceae which is known for its significant polymorphic variations. By observing chromosomal variances, we aimed to shed light on the underlying genetic variations responsible for the observed polymorphism. All the accessions of Senna examined in this study exhibited a diploid chromosome number of 2n = 28. We found variations in the chiasma frequencies of almost all the accessions, particularly concerning the observed number of bivalents, quadrivalents, position of centromere and the presence of the B- chromosome at meiosis-I. Amongst the four accessions studied, two displayed reduced pollen stainability, which seems to be correlated with a lower frequency of chiasmata and the influences of the collection sites, that was confirmed by the regression analysis. Further, RAPD analysis also confirmed the variations in DNA homologous sequences recorded by the presence of variable length of the fragments in all accessions. All the results collectively underscored the existence of genetic diversity within the subpopulation of Senna alexandrina Mill. & may help to comprehend the broader evolutionary processes within the Fabaceae family.